Corporate take-overs and performance: Evidence from the Malaysian equity market / Song Saw Imm ... [et al.]. - Song, Saw Imm; Chu, Ei Yet (2006)
This study seeks to assess the take-over performance of the Malaysian public listed companies from different perspectives, using both market-based and accounting-based models. It also aims to examine managerial motives for take-overs, take-over transaction characteristics and ownership characteristics to infer any possible sources of value creation or possible agency conflicts that could have a profound impact on the post-take-over performance of the combined firms. As large capital transaction affects the vigour of capital market directly, this study focuses on large corporate take-overs, which cost more than RJVl20 million in Malaysia, and full acquisition (100 percent) targets.